Efficacy and safety of intra-articular glucocorticoid injection for postoperative pain control after knee arthroscopy: a systematic review - Changxu Han; Dige Gan; Chenyang Meng; Yi Qiu; Ting Hao (Journal of Orthopaedic Surgery and Research)
Abstract Purpose Pain following arthroscopic knee surgery remains a controversial clinical problem. Intra-articular (IA) glucocorticoid injections have demonstrated the potential to provide better analgesia in some orthopedic surgeries; however, due to the lack of studies, its role in knee arthroscopies remain unclear. This systematic review aimed to evaluate the efficacy and safety of intra-articular glucocorticoids after arthroscopic knee surgery. Methods A systematic review was conducted according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guideline, with literature search performed on Medline, Embase, and the Cochrane Library. This systematic review has been registered with the International Prospective Register of Systematic Reviews (PROSPERO; ID: CRD42024509749). Inclusion criteria included randomized controlled trials published in English comparing IA glucocorticoid to placebo in patients undergoing knee arthroscopy. Risk of bias for all included studies was assessed using the Cochrane Collaboration’s risk of bias tool. Clinical outcomes compared were pain score: visual analogue scale (VAS) or International Knee Documentation Committee (IKDC), time to first analgesia requirement, analgesia consumption, range of motion (ROM), patient satisfaction, and complications. Results A total of 7 studies (3 and 4 with evidence level I and II, respectively) involving 309 patients were included. All studies showed that IA glucocorticoids significantly decreased subjective pain scores. Three studies showed significantly longer duration to first postoperative analgesia use, while 6 showed significantly reduced postoperative analgesic administration with IA glucocorticoid use. Two studies showed significantly increased patient satisfaction with IA glucocorticoid (P = 0.001 and P = 0.01, respectively). No studies showed significant differences in complications such as nausea, vomiting, bradycardia, hypotension, or procedure-related adverse effects between the groups. Conclusion Current available randomized controlled trials suggest that IA glucocorticoids can significantly reduce postoperative pain, delay, and minimize postoperative analgesia use, and improve patient satisfaction. No postoperative complications or adverse events were reported, reflecting its safety as a postoperative analgesic modality.